The Destroyers of Capitalism: Constitutional Amendment Proposal (PEC) nº 69/2019 and the National Strategy for Business and Impact Investing. - Nogueira, Jorge Henrique de Saules (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2021)
From the perspective of Brazilian state interventionism, this article analyses the Constitutional Amendment Proposal (PEC) nº 69/2019 and the policy promoted by the National Strategy for Business and Impact Investing (Enimpacto). PEC nº 69/2019 aims to elevate the so-called solidarity economy to the status of a constitutional principle of the economic order; while Enimpacto, which emerged amid the Environmental, Social, and Governance (ESG) movement, intends to replace the traditional business paradigm based on profit maximization (shareholder) with a new way of doing business, based on the company’s social and environmental responsibility (stakeholder). We argue that these policies result from the Brazilian interventionist system, defined in the Federal Constitution of 1988. The practical implementation of both further distances the country from the capitalist system, bringing it ever closer to the socialist system.